Sex reversal in a child with a 46, X, Yp+ karyotype: support for the existence of a gene(s), located in distal Xp, involved in testis formation. Issue 4 (April 1992) - Ogata, T; Hawkins, J R; Taylor, A; Matsuo, N; Hata, J; Goodfellow, P N
Abstract : We report on a sex reversed Japanese child with a 46, X, Yp+ karyotype, minor dysmorphic features, and no testicular development. The Yp+ chromosome was derived by translocation of an Xp fragment (Xp21-Xp22.3) to Yp11.3. This has resulted in deletion of distal part of the Y chromosome pseudoautosomal region (DXYS15-telomere) and duplication of the X specific region (DXS84-PABX) and proximal part of the pseudoautosomal region (MIC2-DXYS17). No deletion of the Y specific region was detected nor was any mutation found in SRY. Cytogenetic analysis suggests that the proximal part of the Xp fragment is the most distal part of the short arm of the Yp+ chromosome (Xp21—-Xp 22.3::Yp11.3—-Yqter). No chromosomal mosaicism was detected. These results are similar to previous reports of sex reversal in four subjects with a 46, Y, Xp+ karyotype. We conclude that the sex reversal is a direct, or indirect, consequence of having two active copies of the distal part of Xp and may indicate the presence of a gene(s) which acts in the testis determination or differentiation pathway.